Supervisi manajerial pengawas dalam meningkatkan kompetensi manajerial kepala madrasah - Nurkhan Nurkhan (Sharia: Jurnal Kajian Islam, 2022)
This research was motivated by a description of conditions in the field, still weak managerial competence of madrasah principals. The focus of the problem in this study is the management of the managerial supervision of madrasah supervisors to improve the managerial competence of madrasah principals. This study aims to analyze and find empirically about the managerial supervision of madrasah supervisors in improving the managerial competence of the headmaster of madrasah in Sukabumi district. The investigation process is carried out through phenomena that occur in planning, organizing, implementing, evaluating, and supporting managerial supervision, inhibiting factors, and the impact of managerial supervision of madrasah supervisors in improving the managerial competence of madrasah principals. The foundation of philosophy, theory, and basic concepts developed in this study is the managerial supervision of madrasah supervisors in improving the managerial competence of madrasah principals. The methods used to study the data are descriptive analytic methods and qualitative approaches with data techniques based on observations, interviews and documentation. The results of research at the planning, organizing and implementation stages have been carried out by madrasah supervisors, but there are still problems that have not been supported by the analysis of the needs of madrasah principals and there is no structured and managed division of tasks. In the evaluation stage, managerial supervision is carried out as a basis for creating a follow-up program and a supervision program for the following year. The support capacity for managerial supervision is in the form of routine monthly service meetings to adjust the managerial supervision program. Meanwhile, the inhibiting factor for managerial supervision is not in accordance with the theory of supervision because the indicator for the internal inhibiting factor is the ratio of the number of supervisors and the number of madrasas is not balanced. As for or the impact of the results of managerial supervision, the principal has managerial competence as evidenced by the madrasah work program documents, RKAM, and other documents